LEVEL OF COMPLIANCE WITH TREATMENT REGIME OF TYPE 2 DIABETES MELLITUS ON OUTPATIENTS (Vietnam Journal of Community Medicine, 2021)
Objectives: To evaluate the compliance of patients with treatment regime of type 2 diabetes on outpatients at Dong Thap Regional General Hospital. Objects and methods: Retrospective descriptive study on 240 patients diagnosed with type 2 diabetes and outpatient treatment at Dong Thap General Hospital. Results: The percentage of patients who always adhered to the treatment regime was not high: 38.40% of patients always limited the use of fast hyperglycemic foods; 30.28% of patients always limited the intake of high-fat foods; The rate of patients who always ate washy foods was 27.68%, the rate of patients who always limited drinking beer and alcohol was 28.12%, 31.45% of patients always consumed fiber foods. The rate of patients complying with exercise regimes was an average level: 53.48% patients had the regular adherence to exercise regimes. The rate of good compliance of using drugs was an average level of 60.43%, still having 11.30% of patients were poor drug compliance. Conclusion: The proportion of patients who always adhered to the treatment regime was not high. The percentage of patients adhering to the exercise regimen was moderate. The proportion of patients who complied with good drug administration was moderate.
Keywords: Type 2 diabetes, adherence to treatment regimen, outpatient